Interactions and incompatibilities between the active ingredient and the excipient - Ewelina Mundzik-Janczarska; Andrzej Stańczak (Polish Pharmaceutical Society, 2021)
Excipients are important components of the final medicinal product. They perform many important functions as fillers, lubricants, disintegrating agents, stabilizers, emulsifiers, etc., and their presence in the formulation is essential. They facilitate the technological process and improve the drug bioavailability. Their proper selection is necessary to obtain the final product with appropriate physicochemical properties. The excipients are not inert compounds. They undergo many interactions with the drug. The occurrence of chemical interactions as a consequence of the chemical reaction of the active substance with the excipient or its impurities can lead to degradation of the drug (including the formation of toxic degradation products) or reduction of its therapeutic properties. Examples of chemical reactions are reactions with water molecules (including hydrolysis), oxidation, isomerization, and other complex chemical reactions such as Maillard reactions. Physical interactions involving changes in physicochemical parameters such as solubility, alteration in flavor, odor, or color lead to changes in the bioavailability of the drug. Physical drug-excipient interactions (adsorption or complex formation, etc.) are commonly used in the pharmaceutical industry e.g., to improve the solubility of lipophilic substances, thus achieving higher bioavailability. Sometimes they are unintentional, and the occurrence of these phenomena may have a detrimental effect on the final product (changes in color, odor, or flavor, difficult drug release from the excipient complex). Excipients may also affect the drug metabolism by enhancing or inhibiting the activity of cytochrome P450 and P-glycoprotein. In addition, they are also subject to a number of interactions with body fluids. The impurities of excipients are an important aspect of the formulation. The most common impurities are oxides, aldehydes, acids, and metals. Usually, these substances are highly reactive. Therefore, their presence is often the cause of incompatibility. In order to minimize the occurrence of interactions, so-called formulation compatibility tests are performed, and the most effective is the combination of thermoanalytical and non-thermoanalytical (spectroscopic, chromatographic) methods of analysis. Currently, there are no globally harmonized regulatory requirements for excipients, however, organizations such as IPEC are working towards harmonization.